Improving evidence-based practice through preregistration of applied research: Barriers and recommendations. (17th February 2023) - Evans, Thomas Rhys; Branney, Peter; Clements, Andrew; Hatton, Ella
ABSTRACT: Preregistration is the practice of publicly publishing plans on central components of the research process before access to, or collection, of data. Within the context of the replication crisis, open science practices like preregistration have been pivotal in facilitating greater transparency in research. However, such practices have been applied nearly exclusively to basic academic research, with rare consideration of the relevance to applied and consultancy-based research. This is particularly problematic as such research is typically reported with very low levels of transparency and accountability despite being disseminated as influential gray literature to inform practice. Evidence-based practice is best served by an appreciation of multiple sources of quality evidence, thus the current review considers the potential of preregistration to improve both the accessibility and credibility of applied research toward more rigorous evidence-based practice. The current three-part review outlines, first, the opportunities of preregistration for applied research, and second, three barriers – practical challenges, stakeholder roles, and the suitability of preregistration. Last, this review makes four recommendations to overcome these barriers and maximize the opportunities of preregistration for academics, industry, and the structures they are held within – changes to preregistration templates, new types of templates, education and training, and recognition and structural changes.